For duty and honor Tennessee's Mexican War experience - Johnson, Timothy D. 1957- (The University of Tennessee Press, 2018)
"This is the first full-length work on the state's involvement in the Mexican War. Tennessee contributed a huge number of volunteers to the war effort, and Johnson's account not only seeks to describe the military context but also to explore the motivations of Tennessee soldiers. Their notions of duty, a martial mentality and strong sense of masculinity, and the aspirations of a new nationalism all combined to create a culture of honor that was the ideological wellspring for the operation. For Tennesseans, as for many Americans, the war wasn't without controversy, especially as battle casualties mounted, disease spread, the incompetence of military leaders (including Tennessee's own Gideon Pillow) became apparent"...